Pengaruh Dana Bagi Hasil, Dana Alokasi Umum dan Pajak Daerah terhadap Belanja Daerah (Studi Empiris pada Provinsi Banten Periode 2012-2021) - Ramadhani, Dici; Indrawan, I Gede Adi; Juitania, Juitania (BUDGETING : Journal of Business, Management and Accounting, 2023)
This study aims to determine the effect of Profit haring Fund, General Allocation Fund and Regional Tax on Regional Expenditure. The type of research used in this study is quantitative. This research was conducted using data taken from the Central Bureau of Statistics of Banten Province for the 2012-2021 period. The sampling method uses Saturated Sampling with the sample results obtained in this study as many as 40 data. Data testing in this study was assisted by the SPSS 20 program. The results of this study explain that the Production Sharing Fund, General Allocation Fund and Regional Tax simultaneously affect Regional Expenditure. Partially, the Profit Sharing Fund has no effect on Regional Expenditure. The General Allocation Fund affects Regional Expenditure. Local Tax affects Regional Expenditure. Keywords: Profit Sharing Fund, General Allocation Fund, and Local Tax.